2017
DOI: 10.1111/bld.12196
|View full text |Cite
|
Sign up to set email alerts
|

“Tell me what they do to my body”: A survey to find out what information people with learning disabilities want with their medications

Abstract: Accessible summary We gave a questionnaire to self‐advocates who were attending a conference. The questionnaire asked them how they felt about the information they get with their medicine. Fifty‐eight people completed the questionnaire. Many of them said they did not get enough information about their medicine. Most people wanted easy‐read leaflets and pictures. There are many different places to find easy‐read information on the internet. We think they should be collected and checked. We also think that doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 29 publications
0
56
0
Order By: Relevance
“…However, this review suggests that people with intellectual disabilities are not always receiving accessible information about their medication directly from healthcare professionals (Davis et al, 2016;Fish et al, 2017;Flood & Henman, 2015). However, this review suggests that people with intellectual disabilities are not always receiving accessible information about their medication directly from healthcare professionals (Davis et al, 2016;Fish et al, 2017;Flood & Henman, 2015).…”
Section: Accessibility and Delivery Of Informationmentioning
confidence: 96%
See 4 more Smart Citations
“…However, this review suggests that people with intellectual disabilities are not always receiving accessible information about their medication directly from healthcare professionals (Davis et al, 2016;Fish et al, 2017;Flood & Henman, 2015). However, this review suggests that people with intellectual disabilities are not always receiving accessible information about their medication directly from healthcare professionals (Davis et al, 2016;Fish et al, 2017;Flood & Henman, 2015).…”
Section: Accessibility and Delivery Of Informationmentioning
confidence: 96%
“…Extending this, Fish et al (2017) found that people would like information presented in ways other than verbally, that is, photos/ videos of how to use their medication (n = 3), mobile alerts/special alarm as a reminder/timetable (n = 4). They also expressed how aids such as hearing loops/braille/sign language and/or interpreters should be utilized when appropriate (n = 5).…”
Section: Format Of Informationmentioning
confidence: 97%
See 3 more Smart Citations